IMPLEMENTATION AND CHALLENGES OF MUALLAF FOUNDATION FARDHU AIN CLASSES IN THE STATE OF KEDAH - Dr. Syahrul Faizaz Abdullah; Dr. Ssuna Salim; Dr. Mohd Akram Dato’ Dahaman; Dr. Solahuddin Abd Hamid; Dr. Mohd Nizho Abd Rahman (Journal of Islamic, Social, Economics and Development, 2018)
The responsibility of guiding the muallaf rests on the shoulders of all Muslims be itthe individual, society and the State. This is done to ensure that they practice the true teachingsof Islam and maintain their new faith. This responsibility in Malaysia is officially carried outby the Council of Islamic Affairs Department assisted by non-government dakwahorganizations (NGO) such as All Malaysia Muslim Welfare Association (PERKIM), MuslimYouth Movement of Malaysia (ABIM) and Malaysian Chinese Muslim Association (MACMA).This study aims at giving a comprehensive idea about how muallaf programs are conducted inthe Northern State of Kedah. This is a case study whose data were gathered through semistructured interviews, observations and document analysis. These data were analysed throughdescriptive method. The results of the study show that both the government and nongovernment organizations do their level best to teach the muallaf. The study observes that thereare a number of unsatisfactory related issues like lack of cooperation among theseorganizations, unsystematic administrative challenges, lack of sufficient funds and qualifiedtrained personnel. The study concludes that there should be cooperation among theseorganizations in order to make these programs more effective and more efficient, such that anychallenges and problems that crop up will easily identified and effectively and efficientlymanaged.